Helical/multiplanar CT scans - Abdullah, Basri Johan Jeet (Malaysian Medical Association, 2005)
For more than three decades, CT has been an important diagnostic imaging tool. In particular, technologic advances in the last 5 year have influenced the patterns of use CT with the use of CT increasing at a steep rate, The principal technical advancement responsible for this increase has been the use of multidetector CT (MDCT), offering both faster scanning and the potential for higher image quality. The value of MDCT resides in its striking improvement of both spatial and temporal resolution, dua to the thinner slice thickness and faster scan time, For example, it takes more than 30 seconds to scan a 30cm lenght of the abdomen with a single-slice helical CT collimation of 5 mm and pitch of 1.5. It only takes 10 seconds with a four-slice collimation. MDCT provides high-resolution of 2.5mm, and eight seconds with a 16-slice, 0.75mm single-slice collimation. MDCT provides high-resolution images of the entire abdomen within short breath-hold duration. Because the slices are thinner, the z-axis resolution is improved, which anables reconstruction of high-quality 3D or multiplanar reformation images. The role of MDCT in the assessment of liver, pancreatic and other GIT cancers will be presented